Digitizing water management: Toward the innovative use of blockchain technologies to address sustainability. Issue 1 (1st January 2020) - Sriyono, Edy
Abstract: Water has always been considered as a physically scarce resource, particularly in North Africa, Central Asia, West Asia, among others. On the other hand, the current water management system is facing substantial difficulties due to the depletion of resources, the complexity of regulation, as well as the increasing demand of water in society. This article attempts to show the possibility of using blockchain technologies in managing scarce resources, such as water, to address environmental sustainability. Those applications could consolidate the seamless integration of the existing water management system through keen agreements which dwell on the blockchain and take into account automated work processes. It is expected that the implementation of blockchain technology will ensure trust, transparency, and accountability among individuals and other economic actors.